2022
DOI: 10.1002/adma.202208157
|View full text |Cite
|
Sign up to set email alerts
|

Chiral‐Selective Antigen‐Presentation by Supramolecular Chiral Polymer Micelles

Abstract: Chirality is ubiquitous in biological systems, which is closely related to biological functions, life processes, and even the pathogenesis of diseases. However, the interface between the chirality of synthetic materials and organisms, particularly the immune system, remains poorly understood. Here, supramolecular chiral polymer micelles (SCPMs) are prepared by complexing antigenic proteins with chiral amino acid‐modified polyethyleneimine. The introduction of chirality not only reduces the toxicity of cationic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…204 Micelles are a type of nanoparticle that presents antigens and self-assemble into a spherical shape, consisting of block copolymers with amphiphilic segments. 211 In the context of antigen presentation, micelles can serve as antigen carriers that enhance the strength and immunogenicity of the encapsulated antigens. By wrapping antigens within the water-hating core, micelles protect them from degradation, enzymatic activity, and immune recognition, prolonging their presence and enhancing their availability to antigen-presenting cells (APCs).…”
Section: Antigen-presenting Nanoparticle For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…204 Micelles are a type of nanoparticle that presents antigens and self-assemble into a spherical shape, consisting of block copolymers with amphiphilic segments. 211 In the context of antigen presentation, micelles can serve as antigen carriers that enhance the strength and immunogenicity of the encapsulated antigens. By wrapping antigens within the water-hating core, micelles protect them from degradation, enzymatic activity, and immune recognition, prolonging their presence and enhancing their availability to antigen-presenting cells (APCs).…”
Section: Antigen-presenting Nanoparticle For Covid-19mentioning
confidence: 99%
“…Micelles are a type of nanoparticle that presents antigens and self-assemble into a spherical shape, consisting of block copolymers with amphiphilic segments . In the context of antigen presentation, micelles can serve as antigen carriers that enhance the strength and immunogenicity of the encapsulated antigens.…”
Section: Overview On Nanoparticulate Vaccines For Covid-19 In the Dev...mentioning
confidence: 99%
“…[16][17][18][19][20][21][22] Chirality is one of the most important phenomena in nature and plays an important role in the living system. 23,24 However, chiral molecules function in various life processes only in a particular configuration. 25 For example, nucleotides and sugars in biological bodies are D-configurational, while phospholipids and amino acids are L-configurational.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al discovered that d -cysteine-modified surfaces exhibited a weaker capacity in recruiting immune cells and immune activation compared to those coated with l -cysteine . Liu et al demonstrated that the immunoactivation effect of d -histidine-modified polyethylenimine is significantly enhanced compared to its corresponding L-chiral counterpart . Gao’s team and Wei’s team reported materials containing D-amino acids for immune regulation that convert macrophages from pro-inflammatory M1 to anti-inflammatory M2 phenotype. , In general, the utilization of multicomponent materials results in divergent conclusions and even contradictory results.…”
mentioning
confidence: 99%